Designing tools to predict and mitigate impacts on water quality following the Australian 2019/2020 wildfires: Insights from Sydney's largest water supply catchment. (13th May 2021) - Neris, Jonay; Santin, Cristina; Lew, Roger; Robichaud, Peter R.; Elliot, William J.; Lewis, Sarah A.; Sheridan, Gary; Rohlfs, Ann‐Marie; Ollivier, Quinn; Oliveira, Lorena; Doerr, Stefan H.
Abstract: The 2019/2020 Australian bushfires (or wildfires) burned the largest forested area in Australia's recorded history, with major socio‐economic and environmental consequences. Among the largest fires was the 280 000 ha Green Wattle Creek Fire, which burned large forested areas of the Warragamba catchment. This protected catchment provides critical ecosystem services for Lake Burragorang, one of Australia's largest urban supply reservoirs delivering 85% of the water used in Greater Sydney. Water New South Wales (WaterNSW) is the utility responsible for managing water quality in Lake Burragorang. Its postfire risk assessment, done in collaboration with researchers in Australia, the UK, and United States, involved (i) identifying pyrogenic contaminants in ash and soil; (ii) quantifying ash loads and contaminant concentrations across the burned area; and (iii) estimating the probability and quantity of soil, ash, and associated contaminant entrainment for different rainfall scenarios. The work included refining the capabilities of the new WEPPcloud‐WATAR‐AU model (Water Erosion Prediction Project cloud‐Wildfire Ash Transport And Risk‐Australia) for predicting sediment, ash, and contaminant transport, aided by outcomes from previous collaborative postfire research in the catchment. Approximately two weeks after the Green Wattle Creek Fire was contained, an extreme rainfall event ( 276 mm in 72 h) caused extensive ash and sediment delivery into the reservoir. The risk assessment informed on‐ground monitoring and operational mitigation measures (deployment of debris‐catching booms and adjustment of the water supply system configuration), ensuring the continuity of safe water supply to Sydney. WEPPcloud‐WATAR‐AU outputs can prioritize recovery interventions for managing water quality risks by quantifying contaminants on the hillslopes, anticipating water contamination risk, and identifying areas with high susceptibility to ash and sediment transport. This collaborative interaction among scientists and water managers, aimed also at refining model capabilities and outputs to meet managers' needs, exemplifies the successful outcomes that can be achieved at the interface of industry and science. Integr Environ Assess Manag 2021;17:1151–1161. © 2021 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). KEY POINTS: The extreme wildfires of 2019/20 burned 35% of the slopes that surround Sydney's main drinking water reservoir, Lake Burragorang, raising concerns about the viability of maintaining the supply of water to the Sydney area due to the risk of contamination from post‐fire erosion of soil and ash. We applied the newly developed WEPPcloud‐WATAR tool (Water Erosion Prediction Project cloud model—Wildfire Ash Transport And Risk estimation tool) to this catchment to predict risks to water quality from contaminants contained in eroded soil and wildfire ash. This collaboration between scientists and managers served as a test bench and helped in improving model capabilities and in adapting its outputs to water managers' needs. The tool now predicts spatial distribution of ash and pollutants on the hillslopes, loads of ash, soil, and pollutants reaching water assets for single rain events; probabilities of water contamination in the medium term; and location of hotspots for soil, ash, and contaminant transport.